Mechanically matching the rheological properties of brain tissue for drug-delivery in human glioblastoma models. (September 2021) - Parkins, Christopher C.; McAbee, Joseph H.; Ruff, Lisa; Wendler, Astrid; Mair, Richard; Gilbertson, Richard J.; Watts, Colin; Scherman, Oren A.
Abstract: Peptide functionalized hyaluronic acid (HA CF ) cross-linked by cucurbit[8]uril (CB[8]), a new class of drug-delivery reservoirs, is used to enable improved drug bioavailability for glioblastoma tumors in patient-derived xenograft (PDX) models. The mechanical and viscoelastic properties of native human and mouse tissues are measured over 8 h via oscillatory rheology under physiological conditions. Treatment with drug–loaded hydrogels allowed for a significant survival impact of 45 % (55.5–80.5 days). A relationship between the type of PDX tumor formed—a consequence of the heterogeneic nature of GB tumors—and changes in the initial survival is observed owing to greater local pressure from stiffer tumors. These biocompatible and tailorable materials warrant use as drug delivery reservoirs in PDX resection models, where the mechanical properties can be readily adjusted to match the stiffness of local tissue and thus have potential to improve the survival of GB patients. Graphical abstract: HA CF ( x ) is produced via simple, facile chemistries. CB [8] exhibits guest-selective encapsulation of HA CF (10) phenylalanine groups. HA CF (10) is a dynamic, physically cross-linked hydrogel; the gel can be tuned to match the mechanical properties of native brain tissue from human or mouse. The hydrogel can be loaded into a syringe, and extruded due to the shear-thinning properties from CB [8] interactions, then readily self-healing leading to increased survival in PDX mouse models when loaded with a therapeutic compound. (See Supporting Information Video 1). Image 1